State of the world's forests 2001 - State of the world's forests 2001 (Rome, Italy, 2001)
This book provides the most recent picture of the extent and location of forests worldwide. It covers new sectoral developments and key forest-related issues, including an in-depth look at forests and climate change, the conservation of forest biological diversity, and illegal actiovities in the forest sector.
Keywords: forest protection,forest resources,forestry development,forestry policies,forests and forestry